Visible light emissions during flash sintering of 3YSZ are thermal radiation. (October 2022) - Bechteler, Christian; Kirkpatrick, Andrew; Todd, Richard I
Abstract: Flash sintering enables the densification of ceramics at low furnace temperatures in a few seconds by the application of an electric field to the specimen. One of the earliest mechanisms proposed to explain the rapid densification involves the generation of Frenkel defects. Light emission during flash sintering is often interpreted as electroluminescence from electron-hole pair recombination, in support of this mechanism. In this work, experimental investigation of the emissions during flash sintering of the most widely studied ceramic, 3YSZ, shows that the visible spectrum can be explained completely in terms of black body (thermal) radiation resulting from the Joule heating of the specimen rather than electroluminescence. Apparent peaks in the spectrum are experimental artefacts associated with the equipment. There is no evidence in the visible emission spectrum during flash sintering of 3YSZ for electron-hole pair recombination associated with Frenkel pair formation or for any mechanism other than Joule heating. Graphical abstract: Image, graphical abstract